"Have You Noticed any Changes upon your Return"? Vietnamese Alumni After Their Australian University Experiences. Issue 3 (4th May 2017) - Starks, Donna; Nicholas, Howard
Abstract: Many individuals who study abroad return to their home country with the hope of applying new learnings. This paper reports on a videotaped group discussion with three such returnees, in-service English language educators from Vietnam. It considers ways that these educators feel that they have changed through their study abroad experiences and how these changes are accepted and contested after their return to Vietnam by their students, colleagues and the public. By exploring the themes that emerge, we open up discussion about how returnees embrace, negotiate and contest diverse aspects of multiple worlds and the complex and layered nature of post-return identity.